The big combo [videorecording (DVD)] - Wilde, Cornel; Conte, Richard, 1910-1975; Donlevy, Brian; Wallace, Jean, 1923- (2013)
Police Lt. Diamond is told to stop his investigation of suspected Mob boss Mr. Brown as it is costing the department too much money with no hard evidence. Diamond turns to Mr. Brown's girlfriend to get the evidence he needs.